2018
DOI: 10.1038/s41590-018-0083-5
|View full text |Cite|
|
Sign up to set email alerts
|

c-Maf controls immune responses by regulating disease-specific gene networks and repressing IL-2 in CD4+ T cells

Abstract: The transcription factor c-Maf induces the anti-inflammatory cytokine IL-10 in CD4+ T cells in vitro. However, the global effects of c-Maf on diverse immune responses in vivo are unknown. Here we show that c-Maf regulates IL-10 production in CD4+ T cells in TH1 (malaria), TH2 (allergy) and TH17 (autoimmunity) disease models in vivo. Although CD4-targeted Maf-deficient mice showed greater pathology in TH1 and TH2 responses, TH17-mediated pathology was reduced, with accompanying decreased TH17 and increased Foxp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

14
137
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 133 publications
(151 citation statements)
references
References 53 publications
14
137
0
Order By: Relevance
“…There are extensive reports about the transcriptional regulation of IL‐10 production in myeloid cells and T cells, while few reports are available regarding the regulation of IL‐10 in B cells. The expression of c‐Maf has long been considered as a hallmark of macrophages, Th2 and Th17; however, the precise role of c‐Maf during Breg differentiation was unknown before the present study. Our data demonstrated that c‐Maf could effectively increase the production of IL‐10 + Breg cells.…”
Section: Discussionmentioning
confidence: 84%
See 1 more Smart Citation
“…There are extensive reports about the transcriptional regulation of IL‐10 production in myeloid cells and T cells, while few reports are available regarding the regulation of IL‐10 in B cells. The expression of c‐Maf has long been considered as a hallmark of macrophages, Th2 and Th17; however, the precise role of c‐Maf during Breg differentiation was unknown before the present study. Our data demonstrated that c‐Maf could effectively increase the production of IL‐10 + Breg cells.…”
Section: Discussionmentioning
confidence: 84%
“…The cell lineage-specific targets of c-Maf have been identified. It was reported that c-Maf regulated IL-10 production in CD4 + T cells in in vivo disease models involving Th1 cells, 9 Th2 cells, 10 Treg cells 11 and Th17 cells. 12 In this study, we further investigated the function of c-Maf in the expression of IL-10 in Breg cells.…”
Section: Introductionmentioning
confidence: 99%
“…c-Maf plays distinct roles in adaptive versus innate type 17 programming. In Th17 cells, c-Maf is a core regulator of effector genes, directly controlling cytokine, anti-inflammatory, and tissue residency gene expression programs, yet notably, not Rorc master regulator expression (Xu et al, 2009;Ciofani et al, 2012;Aschenbrenner et al, 2018;Gabryšová et al, 2018). In contrast, in innate programming of RORγt + lymphoid effectors, c-Maf directly controls the expression of lineage-defining TFs to influence lineage identity and plasticity.…”
Section: Discussionmentioning
confidence: 99%
“…The MAPK p38 is also activated downstream of TLR signaling and shown to regulate IL-10 production by these cells (Yi et al, 2002;Chi et al, 2006;Kim et al, 2008). Several transcription factors known to regulate the transcription of the Il10 gene in macrophages and DCs are activated downstream of ERK1/2 or p38, as is the case for cAMP response element binding protein (CREB), cyclic AMPdependent transcription factor 1 (ATF1), cFos, and Sp1 (reviewed in Saraiva and O'Garra, 2010;Rutz and Ouyang, 2016;Gabryšová et al, 2018;Ouyang and O'Garra, 2019). Cooperation between ERK and p38 activates the mitogen-and stressactivated protein kinase 1 (MSK1) and MSK2, which promote IL-10 production in TLR4-stimulated macrophages, through the transcription factors CREB and ATF1 (Ananieva et al, 2008).…”
Section: Introductionmentioning
confidence: 99%